Evaluation of Local E-government Maturity in the Lima Metropolitan Area - Dias, Gonçalo Paiva (2020)
This article presents a preliminary evaluation of e-government maturity for 37 district municipalities of the Lima Metropolitan Area, in Peru. A three-dimensional maturity model (with dimensions e-information, e-services; and e-participation) previously used in other studies was applied. Empirical data was obtained using Website content analysis. Descriptive statistics and clustering technics were used to analyze results. The results support the conclusions that the Lima municipalities tend to privilege simpler developments in detriment of more complex ones; that, consequently, the e-information dimension is more developed than the e-service dimension which, in turn, is more developed that the e-participation dimension; and that different profiles of municipalities coexist in what concerns the balance between the three different dimensions of the maturity model. These findings are consistent with other studies that used the same method in a different geography. The results also indicate the need to update the maturity model used and adapt it to the specific Peruvian case.